Quest for Authentic Existence in Marleen Gorris’s Movie Mrs. Dalloway - Bhusal, Damodar (Kaladarpan कलादर्पण, 2022)
The paper attempts to make a cinematographic study of Marleen Gorris’s film Mrs. Dalloway, the screen adaptation of the popular novel Mrs. Dalloway by Virginia Woolf through the perspective of Existentialism introduced by Jean Paul Sartre. The movie by Gorris seems to be a love story but it also portrays the existential quest of the protagonist for the meaningful life or for the authentic existence. In the late nineteenth and early twentieth centuries, in the society of England, Clarissa determines herself to choose a life of her own choice for which she has to face many objections, but her courage to go beyond that and make own choice of life is the main purpose discussed here. This research is studied through cinematographic analytic way, which is drawn upon the concept of authentic existence relating to the theory of Existentialism. This study comes to the conclusion that to live the meaningful life or to lead a life of meaningful existence Clarissa puts her love behind, and marries Richard for her own authentic sake.